Scientific evidence for efficiency of medicinal plants in otorhinolaryngology - Vladimir A. Kurkin; Elena V. Avdeeva; Olga E. Pravdivtseva; Anna V. Kurkinа; Natalya R. Varina; Viktoriya V. Stenyaeva; Anastasiya S. Tsybina; Sergei V. Pervushkin (Наука и инновации в медицине, 2021)
Objectives to provide scientific evidence for rational use of herbal medicines in otorhinolaryngological practice.